The role of noncoding RNAs in cancer lipid metabolism - Wang, Ye; Li, Qian; Wang, Song; Wang, Bi-jun; Jin, Yan; Hu, Hao; Fu, Qing-sheng; Wang, Jia-wei; Wu, Qing; Qian, Long; Cao, Ting-ting; Xia, Ya-bin; et al. (Frontiers in Oncology, 2022)
Research on noncoding ribonucleic acids (ncRNAs) is mostly and broadly focused on microRNAs (miRNAs), cyclic RNAs (circRNAs) and long ncRNAs (lncRNAs), which have been confirmed to play important roles in tumor cell proliferation, invasion and migration. Specifically, recent studies have shown that ncRNAs contribute to tumorigenesis and tumor development by mediating changes in enzymes related to lipid metabolism. The purpose of this review is to discuss characterized ncRNAs involved in the lipid metabolism of tumors to highlight ncRNA-mediated lipid metabolism-related enzyme activity in malignant tumors and its importance to tumor development. In this review, we describe the types of ncRNA and the mechanism of tumor lipid metabolism and analyze the important role of ncRNA in tumor lipid metabolism and its future prospects from the perspectives of ncRNA biological function and lipid metabolic enzyme classification. However, several critical issues still need to be resolved. Since ncRNAs can affect tumor processes by regulating lipid metabolism enzymes, in the future, we can study the unique role of ncRNAs from four aspects: disease prevention, detection, diagnosis and treatment. Therefore, in the future, the development of ncRNA-targeted therapy will become a hot direction and shoulder a major task in the medical field.